2018
DOI: 10.1089/jayao.2017.0112
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship Care Planning for Young Adults After Cancer Treatment: Understanding Care Patterns and Patient-Reported Outcomes

Abstract: YAS report high satisfaction with the online SCP, as well as a high symptom burden, although the latter were reported less than for AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Most studies that examined age and cognitive impairments found that older age was associated with higher levels of impairment 31,36,45,46,56 . However, one article reported that younger survivors had more cognitive impairment 48 , one found that younger survivors reported worse functioning 44 , and one found no difference in cognitive function between older and younger survivors 28 .…”
Section: Agementioning
confidence: 99%
“…Most studies that examined age and cognitive impairments found that older age was associated with higher levels of impairment 31,36,45,46,56 . However, one article reported that younger survivors had more cognitive impairment 48 , one found that younger survivors reported worse functioning 44 , and one found no difference in cognitive function between older and younger survivors 28 .…”
Section: Agementioning
confidence: 99%
“…While SCPs have been integrated into adult oncology standard of care, few studies have described their use in pediatrics 3,4 . SCPs are documents that report on health risks (ie, late effects) and recommendations for follow‐up care, health promotion, and well‐being 5 .…”
Section: Introductionmentioning
confidence: 99%
“…While SCPs have been integrated into adult oncology standard of care, few studies have described their use in pediatrics. 3,4 SCPs are documents that report on health risks (ie, late effects) and recommendations for follow-up care, health promotion, and well-being. 5 SCPs for AYA may be especially important given AYA are assuming more responsibility for health care, may lack adequate knowledge of their childhood cancer history and possible late effects, [6][7][8][9] report reduced health-related quality of life, 10 and are at risk for suboptimal health behaviors.…”
Section: Introductionmentioning
confidence: 99%